Expression analysis of PIN family genes in Chinese hickory reveals their potential roles during grafting and salt stress - Yang, Ying; Mei, Jiaqi; Chen, Juanjuan; Yang, Ying; Gu, Yujie; Tang, Xiaoyu; Lu, Huijie; Yang, Kangbiao; Sharma, Anket; Wang, Xiaofei; Yan, Daoliang; Wu, Rongling; et al. (Frontiers in Plant Science, 2022)
Grafting is an effective way for improvement of Chinese hickory while salt stress has caused great damage for Chinese hickory industry. Both graft operation and salt stress have been regarded as the main abiotic stress types for Chinese hickory. However, how Chinese hickory responds to graft operation and salt stress is less studied. Auxin has been proved to play essential roles in stress responses through its re-distribution regulation mediated by polar auxin transporters, including PIN-formed (PIN) proteins. In this study, the PIN family genes in Chinese hickory (CcPINs) were identified and structurally characterized for the first time, and their expression profiles in response to grafting and salt stress were determined. A total of 11 CcPINs with the open reading frames (ORFs) of 1026 bp to 1983 bp were identified. Transient transformation in tobacco leaves demonstrated that CcPIN1a, CcPIN3, and CcPIN4 were localized on the plasma membrane. There were varying phylogenetic relationships between CcPINs and homologous genes in different species, but the closest relationships were with those in Carya illinoinensis and Juglans regia. Conserved N- and C-terminal transmembrane regions as well as sites controlling the functions of CcPINs were detected in CcPINs. Five types of cis-acting elements, including hormone- and stress-responsive elements, were detected on the promoters of CcPINs. CcPINs exhibited different expression profiles in different tissues, indicating their varying roles during growth and development. The 11 CcPINs responded differently to grafting and salt stress treatment. CcPIN1a might involve regulation of the grafting process, while CcPIN1a and CcPIN8a were related to regulation of salt stress in Chinese hickory. Our results will lay the foundation for understanding the potential regulatory functions of CcPIN genes during grafting and under salt stress treatment in Chinese hickory.